A novel zinc‐binding alcohol dehydrogenase 2 from Arachis diogoi, expressed in resistance responses against late leaf spot pathogen, induces cell death when transexpressed in tobacco. Issue 3 (25th February 2016) - Kumar, Dilip; Rampuria, Sakshi; Singh, Naveen Kumar; Kirti, Pulugurtha B.
Abstract : A novel zinc‐binding alcohol dehydrogenase 2 (AdZADH2) was significantly upregulated in a wild peanut, Arachis diogoi treated with conidia of late leaf spot (LLS) pathogen, Phaeoisariopsis personata . This upregulation was not observed in a comparative analysis of cultivated peanut, which is highly susceptible to LLS. This zinc‐binding alcohol dehydrogenase possessed a Rossmann fold containing NADB domain in addition to the MDR domain present in all previously characterized plant ADH genes/proteins. Transient over‐expression of AdZADH2 under an estradiol inducible promoter (XVE) resulted in hypersensitive response (HR)‐like cell death in tobacco leaf. However, the same level of cell death was not observed when the domains were transiently expressed individually. Cell death observed in tobacco was associated with overexpression of cell death related proteins, antioxidative enzymes such as SOD, CAT and APX and pathogenesis‐related (PR) proteins. In A. diogoi, AdZADH2 expression was significantly upregulated in response to the plant signaling hormones salicylic acid, methyl jasmonate, and sodium nitroprusside.